PRODUCTION AND DEVELOPMENT OF A POLYMER COMPOSITION RECEPTION BASED ON WOOD INDUSTRY WASTE - Umarov Fakhriddin; Khoshimov Kadirjon; Ergashev Yorkinjon; Aliev Sunnatilla; Egamberdiev Elmurod (American Journals Publishing, 2024)
The scientific significance of the results of this research is that the scientific basis of the relationship between the physico-chemical and structural properties of wood-polymer composite materials obtained from various wood wastes and primary and secondary polyvinyl chloride, and the quality indicators of the products included in the composition has been created. Based on local raw materials, wood-polymer composite materials were obtained, and the obtained materials are used as the main raw material in the furniture industry, i.e. wood shavings (DStP), sheet-like main raw material replacing medium-density fiberboard (MDF) boards, and decorative material for exterior facade parts of buildings in the field of construction, yard it is recommended to use it as a board panel for terraces and formwork (formwork) for concrete foundations during the construction process.
Keywords: Wood-polymers, composites, primary polyvinyl chloride, secondary polyvinyl chloride, wood chipboard (WCP), medium density fiberboard (MDF) boards.